Antidiabetic activity of wogonin isolated from Tetracera indica Merr. leaves extract in streptozotocin-nicotinamide induced diabetic rats - Zulkefli, Nabilah; Ahmed, Qamar Uddin; Bunawan, Hamidun; Hamezah, Hamizah Shahirah; Fakurazi, Sharida; Ahmmad, Siti Nor Zawani; Sarian, Murni Nazira (Malaysian Institute of Chemistry, 2022)
The leaves of Tetracera indica Merr. (Dilleniaceae) have been used to treat diabetes in Malaysia. However, the active principles responsible for the leaf’s antidiabetic effect are yet to be confirmed and evaluated through an in vivo investigation. Hence, a phenolic compound as a flavonoid (wogonin) was isolated as a major compound from the leaves methanol extract and subjected to antidiabetic evaluation. Initially, the powdered leaves were macerated with methanol for 72 h. The resultant methanol extract was subjected to column chromatography to isolate the pure wogonin. Its structure was elucidated through 1H- & C-13 NMR spectral analysis. Finally, the wogonin was orally given to streptozotocin-nicotinamide (STZ-NA) induced diabetic rats at three different doses (25, 40, 80 mg/kg b.w.). The histological alteration of vital organs, insulin release, biochemical assays, and blood glucose serum were evaluated and compared to standard hypoglycaemic drug i.e., metformin (0.5 mg/kg b.w.). Data of the blood glucose serum of rats treated with wogonin at 40 and 80 mg/kg b.w. revealed a significant decrease in blood glucose when compared to the diabetic control (p<0.05). Biochemical analyses for all doses displayed no significant difference when compared to the normal group and positive control (p>0.05) for triglyceride, total cholesterol, high-density, and low-density lipoprotein. However, the results were significantly different for triglyceride, total cholesterol, high-density, and low-density lipoprotein when compared to diabetic control (p<0.05). In addition, wogonin at 40 mg/kg b.w. was found to enhance insulin secretion by day 30. The histopathology data of the pancreas showed that wogonin at 40 and 80 mg/kg b.w. was observed to regenerate pancreatic β-cells in diabetic rats without demonstrating any liver and kidney toxicities. The results indicated that wogonin possesses an in vivo antidiabetic property and therefore might provide a lead for the synthesis of a safe natural product-based antidiabetic agent.